Investigation of ABCA1 C69T and G-191C polymorphisms in coronary artery disease - (:unkn) unknown (INT INST ANTICANCER RESEARCH, 2008)
Background: Defects of lipoprotein metabolism are common risk factors for coronary artery disease. The ATP binding cassette transporter 1 (ABCA1) plays an important role in carrying cholesterol from peripheral tissues to the liver. The role of ABCA1 C69T and G-191C gene polymorphisms on plasma lipid levels of patients with Coronary artery disease was investigated. Patients and Methods: Seventy-seven patients with coronary artery disease and fifty, healthy controls were studied. Gene polymorphisms were determined by polymerase chain rcaction-restriction fragment length polymorphism method. Results: No differences in the distribution of C69T and G-191C polymorphisms were observed in the study groups. Plasma triacylglycerol and VLDL-cholesterol levels were shown to be higher in the patient group with the C69T CC genotype compared to these patients with the CT genotype. The C69T polymorphism was associated with HDL-cholesterol levels, which insignificantly increased in the order of the CC>CT>TT genotypes in our study. No association was found between G-191C genotype and lipid levels. Conclusion: The results of our study suggested that polymorphisms of ABCA1 C69T polymorphism may be associated with plasma triacylglycerol and VLDL-cholesterol levels in coronary artery patients.
Keywords: lipoproteins; coronary artery disease; genetic; polymorphism; ABCA1; VLDL; cholesterol; DENSITY-LIPOPROTEIN-CHOLESTEROL; MYOCARDIAL-INFARCTION; HDL-CHOLESTEROL; TANGIER-DISEASE; HEART-DISEASE; PLASMA; GENE; MEN; DEFICIENCY; MUTATIONS